Post-Exercise Skeletal Muscle Glycogen Related to Plasma Cytokines and Muscle IL-6 Protein Content, but not Muscle Cytokine mRNA Expression - Nieman, David C.; Zwetsloot, Kevin A.; Meaney, Mary Pat; Lomiwes, Dominic D.; Hurst, Suzanne M.; Hurst, Roger D. (Frontiers in Nutrition, 2015)
Objectives: The purpose of this study was to correlate post-exercise muscle glycogen levels with changes in plasma cytokine, and muscle mRNA cytokine expression and protein content. Methods: Twenty-four male runners (age 36.5±1.8 y, VO2max 60.0±1.5 ml.kg.-1min-1) ran twice (separated by 4 weeks) on treadmills to exhaustion at 70% VO2max (average time and distance of 2.24±0.09 h and 24.9±1.1 km). Muscle biopsies from the vastus lateralis and blood samples were collected before and after each run, with IL-6, IL-8, and MCP-1 measured in muscle (mRNA and protein) and plasma. Data from the two runs were averaged. Results: Participants experienced a 35.3±4.2% decrease (P<0.001) in skeletal muscle glycogen content (67.5±2.8 to 44.3 ±3.7 mmol/kg wet weight). Muscle mRNA expression for IL-6, IL-8, and MCP-1 increased 7.34±0.90-, 13.9±2.3-, and 4.10±0.60- fold, respectively (all, P<0.001). Skeletal muscle IL-6, IL-8, and MCP-1 protein content increased 35.8±10.6%, 80.6±12.1%, and 105±17.9%, respectively (all P≤0.005). Plasma IL-6, IL-8, and MCP-1 increased 47.1±10.0-, 2.6±0.3-, and 1.6±0.1-fold, respectively (all, P<0.001). Post-exercise muscle glycogen concentrations were negatively correlated with run time to exhaustion (r=-0.70, P<0.001), and changes in muscle IL-6 protein content (r=-0.44, P=0.049), plasma IL-6 (r=-0.72, P<0.001), IL-8 (r=-0.60, P=0.002), and MCP-1 (r=-0.589, P=0.002), but not with changes in muscle IL-8 and MCP-1 protein content, or muscle mRNA expression for IL-6, IL-8, and MCP-1. Conclusions: Prolonged and intensive running increased muscle mRNA expression, muscle protein content, and plasma levels for IL-6, IL-8, and MCP-1, and post-run muscle glycogen levels were most strongly related to plasma cytokine levels.